Efeito do treino de leitura na leitura e escrita recombinativas - Marangoni, Angela Maria Catarina (2007)
The goal of the present work was to test a procedure where training word reading was followed by the exposure to the word and word writing. Participants were 3 children with developmental deficits. An initial assessment of the children reading and writing repertoires was conducted by asking them to read and writer 36 dictated words (12 of them were training words and the other 24 words were formed by recombination of the syllables of the training words). Training words were assigned to 3 sets and reading each set of words was tested, trained and tested again. During training correct reading responses were followed by praise and small gifts. Two consecutive correct reading responses of a word led to the training of a new word. Wrong reading responses were followed by the experimenter reading of the word and the repetition of the same trial. When training of a set of 4 words was completed, the word exposure followed: each word was shown to the participant who was asked not to read them allowed. Finally each word was dictated and the participant was asked to write it. After training of each set of words a test was conducted: participants were asked to read and to write the 36 words .Results showed that training had an effect on word reading, bur not necessarily over writing, although the number or correct writing responses increased with word exposure. Error analysis showed that training led to an increase of correct syllable reading and writing, but not to correct reading and writing of new words, comprised of the trained syllables